PENGEMBANGAN DESA WISATA BUDAYA BERBASIS KAIN TENUN TRADISIONAL DI DESA SUKARARA KABUPATEN LOMBOK TENGAH - Welaya Aftina; I Wayan Kiki Sanjaya; Francisca Titing Koerniawaty (Bajang Institute, 2024)
Indonesia has a rich cultural diversity, traditions and craftsmanship that has great potential to be an attractive cultural tourist destination. A rich tradition and craftsmanship has great potential to be an attractive cultural tourist destination. One of the valuable assets in enhancing the attractiveness of cultural tourism is the fabric art that has become an important part of Indonesian culture and inherits a rich historical tradition. To participate in sustainable tourism development, therefore, the objectives in this study are to identify the advantages and characteristics of weaving crafts, analyze constraints and design a development model in Sukarara Village, Central Lombok Regency. The research uses descriptive qualitative methods with data collection techniques through observation techniques, interviews, and documentation. The results of the research show that songket weaving in Sukarara Village has advantages and characteristics that lie in its meaning and symbols, as well as patterns and motifs inspired by the environment. However, the obstacles are the lack of promotion of fabric and the change of style with the presence of modernization and globalization. From the identification of the advantages and obstacles in the development of Sukarara Village and the obstacles based on the component 4A in tourism (attraction, amenities, accessibility, dan ancillary) and the development design model uses a need analyze